Risk attitude assessment using roulette and a supply chain simulation. (5th October 2022) - Atkins, Ryan; Drake, Matthew
ABSTRACT: Many topics that are taught in supply chain management (SCM) programs include elements of variability and risk. With quantitative tools in particular, it is assumed that the decision makers using the tools are risk neutral, which is typically not the case in real‐life decision situations. The topic of an individual's attitude toward risk has received limited attention in SCM literature and is not a high‐profile topic in SCM textbooks. The teaching exercise presented in this paper uses two games—roulette and a SCM simulation—to provide students with an assessment of their own attitude toward risk, and in doing so, facilitates a classroom discussion of risk and risk attitude. These games were developed by the authors and can be played either within Excel or a web application.